PENINGKATAN NILAI PERUSAHAAN DAN PROFITABILITAS PERUSAHAAN MENGGUNAKAN STRUKTUR MODAL YANG DIMODERASI OLEH GOOD CORPORATE GOVERNANCE - Annazul Triasari (Jurnal Riset Bisnis Indonesia, 2015)
This study aims to examine and analyze the capital structure and profitability in the Islamic Jakartacompanies Index (JII) that go public in Indonesia Stock Exchange.The researchers used 14 companies belonging to the Jakarta Islamic Index (JII) in IndonesiaStock Exchange. This type of research is explanatory research. Data collection techniques usingdocumentary techniques. Data used in this research is secondary data from financial statementspublished by the company were successively joined the Islamic Indonesian companies Index (III)during the years 2010 - 2013. Furthermore, the data collected was analyzed quantitatively by usingmultiple regression analysis using SPSS 20.0vers The results showed that the variables of capitalstructure (DER) significantly affects Profitability and variables profitability significantly influence tothe company’s value, in this study the researchers added a variable as a variable of Good CorporateGovernance moderating and serves to strengthen the capital structur variables on firm value (PBV).Keywords: Capital Structure (DER), Profitability (ROE), Good Corporate Governance andEnterprise Value (PVB).